Secondary battery and electric device
The secondary battery design with distinct separators and ceramic coatings addresses both cycle and safety performance challenges by enhancing ion conductivity and adhesion, respectively, thereby improving overall battery performance.
Patent Information
- Application Number
- CN202411216668.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-20
AI Technical Summary
Existing secondary batteries, such as lithium-ion batteries, face challenges in simultaneously improving cycle performance and safety performance when enhancing the diaphragm's performance.
A secondary battery design incorporating a first separator with a water-based adhesive layer and good ion conductivity, and a second separator with an oily adhesive layer and strong adhesion, along with ceramic coatings on both, to address electrolyte bridge breaking and safety concerns.
The combination of separators with different properties enhances both cycle performance by reducing electrolyte bridge breaking and safety performance by improving puncture resistance and lithium deposition issues.
Smart Images

Figure CN119170854A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] Secondary batteries, such as lithium-ion batteries, have the advantages of high energy density, long cycle life, low self-discharge rate and environmental protection, and have been widely used in aviation, aerospace, navigation, electric vehicles and other fields. The performance of the diaphragm in lithium-ion batteries determines the interface structure and internal resistance of lithium-ion batteries, and directly affects the capacity, cycle and safety performance of lithium-ion batteries. Diaphragms with excellent performance play an important role in improving the comprehensive performance of lithium-ion batteries. At present, when improving the performance of lithium-ion batteries through diaphragms, its cycle performance and safety performance are usually difficult to take into account at the same time. Summary of the invention
[0003] The purpose of this application is to provide a secondary battery and an electrical device to take into account both the cycle performance and safety performance of the secondary battery. The specific technical solution is as follows:
[0004] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0005] The first aspect of the present application provides a secondary battery, which includes an electrode assembly of a wound structure, the electrode assembly including a positive electrode sheet, a negative electrode sheet, a first separator and a second separator, the negative electrode sheet is located between the first separator and the second separator; the negative electrode sheet includes a negative electrode collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative electrode collector in the thickness direction, the first separator is adjacent to the first negative electrode material layer, and the second separator is adjacent to the second negative electrode material layer; the first separator includes a first base film and an aqueous adhesive layer, the aqueous adhesive layer is arranged on at least one side of the first base film, and one layer of the aqueous adhesive layer is in direct contact with the first negative electrode material layer; the second separator includes a second base film and an oily adhesive layer, the oily adhesive layer is arranged on at least one side of the second base film, and one layer of the oily adhesive layer is in direct contact with the second negative electrode material layer. The first diaphragm has good ion conductivity and relatively weak adhesion, which is conducive to reducing the electrolyte bridge breaking problem in the later stage of the cycle, thereby improving the cycle performance of the secondary battery; the second diaphragm has good adhesion and strong puncture resistance, which is conducive to improving the safety performance of the secondary battery. Therefore, the combination of the first diaphragm and the second diaphragm is conducive to taking into account both the cycle performance and safety performance of the secondary battery.
[0006] In some embodiments of the present application, the first diaphragm further includes a first ceramic coating, which is disposed on the side of the first base film away from the first negative electrode material layer, and the first ceramic coating is located between the first base film and the aqueous adhesive layer; and / or, the second diaphragm further includes a second ceramic coating, which is disposed on the side of the second base film away from the second negative electrode material layer, and the second ceramic coating is located between the second base film and the oily adhesive layer. The introduction of the first ceramic coating and / or the second ceramic coating can further improve the cycle performance of the secondary battery, so that the combination of the above-mentioned first diaphragm and the second diaphragm is more conducive to taking into account both the cycle performance and safety performance of the secondary battery.
[0007] In some embodiments of the present application, along the winding direction of the electrode assembly, the length of the first negative electrode material layer is greater than the length of the second negative electrode material layer. The length of the first negative electrode material layer is greater than the length of the second negative electrode material layer, which is conducive to the negative electrode sheet of the secondary battery absorbing more electrolyte and reducing the risk of cycle bridge failure.
[0008] In some embodiments of the present application, the electrode assembly includes a straight area and a corner area, in which a positive electrode sheet corner section is adjacent to a first negative electrode material layer corner section, the positive electrode sheet corner section is farther away from the winding center of the electrode assembly than the first negative electrode material layer corner section, and the first diaphragm is located between the positive electrode sheet corner section and the first negative electrode material layer corner section. The first diaphragm and the second diaphragm with different characteristics are used in the electrode assembly, each of which has different advantages, which is conducive to improving the lithium deposition and interface problems of the secondary battery in the corner area, further improving the cycle performance of the secondary battery, and making the cycle performance and safety performance of the secondary battery better balanced.
[0009] In some embodiments of the present application, the aqueous adhesive layer includes at least one of aqueous polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber or aqueous polyacrylate; and / or, the oily adhesive layer includes at least one of oily polyvinylidene fluoride, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer. By selecting the above materials, it is beneficial to improve the bonding force between the first diaphragm and the positive electrode plate, between the first diaphragm and the negative electrode plate, between the second diaphragm and the positive electrode plate, and between the second diaphragm and the negative electrode plate, strengthen the interface between the above two, facilitate the transmission of lithium ions, and improve the cycle performance of the secondary battery; at the same time, it reduces the possibility of the first ceramic coating and the second ceramic coating falling off, thereby being more conducive to taking into account the cycle performance and safety performance of the secondary battery.
[0010] In some embodiments of the present application, the coating weight CW1 of the aqueous adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm2 , and / or, the coating weight CW2 of the oily adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm 2 By regulating CW1 and / or CW2 within the scope of this application, it is beneficial to strengthen the interface between the first diaphragm and the positive electrode sheet and / or the negative electrode sheet, and the interface between the second diaphragm and the positive electrode sheet and / or the negative electrode sheet, which is beneficial to the transmission of lithium ions and can further improve the cycle performance of the secondary battery.
[0011] In some embodiments of the present application, the porosity P1 of the first base film is greater than the porosity P2 of the second base film, 40%≤P1≤70%, 5%≤P2≤50%. In some embodiments of the present application, 50%≤P1≤60%, 10%≤P2≤40%. By regulating the porosity P1 of the first base film and the porosity P2 of the second base film within the scope of the present application, the mechanical strength of the first diaphragm and the second diaphragm is high, and the safety performance of the secondary battery can be further taken into account.
[0012] In some embodiments of the present application, the pore size D1 of the first base film is larger than the pore size D2 of the second base film, 80nm≤D1≤700nm, 50nm≤D2≤200nm. In some embodiments of the present application, 250nm≤D1≤520nm, 100nm≤D2≤150nm. By regulating the pore size D1 of the first base film and the pore size D2 of the second base film within the scope of the present application, the mechanical strength of the first diaphragm and the second diaphragm is higher, and the safety performance of the secondary battery can be further taken into account.
[0013] In some embodiments of the present application, the coating weight CW1' of the first ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 , and / or, the coating weight CW2' of the second ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 Regulating CW1' and / or CW2' within the above range is beneficial to increasing the liquid retention of the first diaphragm and / or the second diaphragm, thereby improving the liquid storage performance of the first diaphragm and / or the second diaphragm, and is beneficial to further taking into account the cycle performance of the secondary battery.
[0014] In some embodiments of the present application, the first ceramic coating includes first ceramic particles, the second ceramic coating includes second ceramic particles, and the first ceramic particles and the second ceramic particles each independently include at least one of aluminum oxide, boehmite, silicon oxide, magnesium oxide, titanium oxide, tin oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, or calcium hydroxide. The type of the first ceramic particles in the first ceramic coating and the type of the second ceramic particles in the second ceramic coating are within the scope of the present application, which can further improve the liquid retention capacity of the first diaphragm and the second diaphragm, improve the interface problem caused by insufficient electrolyte between the positive electrode and the negative electrode, and thus further improve the cycle performance of the secondary battery.
[0015] In some embodiments of the present application, the thickness H1 of the first separator is 7.5 μm to 15.0 μm, and the thickness H2 of the second separator is 6.0 μm to 13.0 μm. By adjusting the thickness H1 of the first separator and the thickness H2 of the second separator within the above range, the secondary battery obtained has a high energy density while taking into account both cycle performance and safety performance.
[0016] A second aspect of the present application provides an electrical device, which includes the secondary battery in any of the aforementioned embodiments.
[0017] Beneficial effects of this application:
[0018] The present application provides a secondary battery, which includes an electrode assembly of a winding structure, the electrode assembly includes a positive electrode sheet, a negative electrode sheet, a first separator and a second separator, the negative electrode sheet is located between the first separator and the second separator; the negative electrode sheet includes a negative current collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative current collector in the thickness direction, the first separator is adjacent to the first negative electrode material layer, and the second separator is adjacent to the second negative electrode material layer; the first separator includes a first base film and a water-based adhesive layer, the water-based adhesive layer is arranged on at least one side of the first base film, wherein one layer of the water-based adhesive layer is in direct contact with the first negative electrode material layer; the second separator includes a second base film and an oily adhesive layer, the oily adhesive layer is arranged on at least one side of the second base film, wherein one layer of the oily adhesive layer is in direct contact with the second negative electrode material layer. The first separator includes two layers of water-based adhesive layers, and the second separator includes two layers of oily adhesive layers, the oily adhesive layers have stronger adhesive force than the water-based adhesive layers, and the water-based adhesive layers have stronger ion conductivity than the oily adhesive layers. Therefore, the first base film has good ion conductivity and relatively weak adhesion, which is conducive to reducing the electrolyte bridge breaking problem in the later stage of the cycle, and thus is conducive to improving the cycle performance of the secondary battery; the second base film has good adhesion and strong puncture resistance, which is conducive to improving the safety performance of the secondary battery. Therefore, the combination of the first diaphragm and the second diaphragm is conducive to taking into account both the cycle performance and safety performance of the secondary battery.
[0019] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0021] Figure 1 A schematic diagram of the cross-sectional structure of a wound structure electrode assembly wound along the W direction in one embodiment of the present application along its own thickness direction;
[0022] Figure 2 This is a schematic diagram of a cross-sectional structure of an electrode assembly in another embodiment of the present application after it is unfolded along its thickness direction;
[0023] Figure 3 This is a schematic diagram of the cross-sectional structure of an electrode assembly along its thickness direction after it is unfolded in one embodiment of the present application;
[0024] Figure 4 for Figure 1 A partial enlarged view of point A in the middle. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0026] The first aspect of the present application provides a secondary battery, which includes an electrode assembly of a wound structure. Specifically, Figure 1 As shown, the electrode assembly 100 is a wound structure, and the electrode assembly 100 includes a first separator 10, a second separator 20, a negative electrode plate 30 and a positive electrode plate 40. The electrode assembly 100 also includes a straight area 102 and a corner area 101. In the present application, the straight area refers to the straight part of the electrode assembly, and the corner area refers to the curved part of the electrode assembly.
[0027] like Figure 2As shown, the electrode assembly 100 includes a first separator 10, a second separator 20, a negative electrode plate 30 and a positive electrode plate 40, wherein the negative electrode plate 30 is located between the first separator 10 and the second separator 20. The negative electrode plate 30 includes a negative electrode collector 31 and a first negative electrode material layer 32 and a second negative electrode material layer 33 located on both sides of the thickness direction of the negative electrode collector 31, the first separator 10 is adjacent to the first negative electrode material layer 32, and the second separator 20 is adjacent to the second negative electrode material layer 33. The first separator 10 includes a first base film 11 and a water-based adhesive layer 12, and the water-based adhesive layer 12 is arranged on both sides of the first base film 11, that is, the first separator 10 includes two layers of water-based adhesive layers 12, and one of the water-based adhesive layers 12 is in direct contact with the first negative electrode material layer 32. The second separator 20 includes a second base film 21 and an oily adhesive layer 22, and the oily adhesive layer 22 is arranged on both sides of the second base film 21, that is, the second separator 20 includes two layers of oily adhesive layers 22, and one of the oily adhesive layers 22 is in direct contact with the second negative electrode material layer 33. The positive electrode sheet 40 includes a positive electrode collector 41 and positive electrode material layers arranged on both surfaces of the positive electrode collector 41, and the positive electrode material layers include a first positive electrode material layer 42 and a second positive electrode material layer 43. It can be understood that the water-based adhesive layer 12 can also be arranged on one side of the first base film 11, that is, the first separator 10 includes a layer of water-based adhesive layer 12, and the water-based adhesive layer 12 is in direct contact with the first negative electrode material layer 32; the oily adhesive layer 22 is arranged on one side of the second base film 21, that is, the second separator 20 includes a layer of oily adhesive layer 22, and the oily adhesive layer 22 is in direct contact with the second negative electrode material layer 33.
[0028] The inventors have found that the present application is conducive to giving full play to the advantages of each layer by selecting the above-mentioned first diaphragm 10 and the second diaphragm 20 for use in combination, so as to take into account the cycle performance and safety performance of the secondary battery. Specifically, the first diaphragm 10 includes a water-based adhesive layer 12, and the second diaphragm includes an oily adhesive layer 22. The adhesive force of the oily adhesive layer 22 is stronger than that of the water-based adhesive layer 12, and the ion conductivity of the water-based adhesive layer 12 is stronger than that of the oily adhesive layer 22. Therefore, the first base film 11 has good ion conductivity and relatively weak adhesion, which is conducive to reducing the electrolyte bridge breaking problem that occurs in the late cycle, and thus is conducive to improving the cycle performance of the secondary battery; the second base film 21 has good adhesion and strong puncture resistance, which is conducive to improving the safety performance of the secondary battery. Therefore, the use of the first diaphragm 10 and the second diaphragm 20 in combination is conducive to taking into account the cycle performance and safety performance of the secondary battery.
[0029] In the present application, a water-based adhesive layer refers to an adhesive layer made of a water-based adhesive as the main material, which has good corrosion resistance and a relatively rough surface; an oily adhesive layer refers to an adhesive layer made of an oily adhesive as the main material, which has good oil resistance and a smooth surface. Among them, a water-based adhesive refers to an adhesive with hydrophilic properties, and an oily adhesive refers to an adhesive with lipophilic properties. In some embodiments of the present application, such as Figure 3 As shown, the electrode assembly 100 includes a first separator 10, a second separator 20, a negative electrode plate 30 and a positive electrode plate 40, wherein the negative electrode plate 30 is located between the first separator 10 and the second separator 20. The negative electrode plate 30 includes a negative electrode current collector 31 and a first negative electrode material layer 32 and a second negative electrode material layer 33 located on both sides of the negative electrode current collector 31 in the thickness direction, wherein the first separator 10 is adjacent to the first negative electrode material layer 32, and the second separator 20 is adjacent to the second negative electrode material layer 33. The first diaphragm 10 includes a first base film 11, an aqueous adhesive layer 12 and a first ceramic coating 13. The aqueous adhesive layer 12 is arranged on both sides of the first base film 11, and the first ceramic coating 13 is arranged on the side of the first base film 11 away from the first negative electrode material layer 32. The first ceramic coating 13 is located between the first base film 11 and the aqueous adhesive layer 12. That is, the first diaphragm 10 includes two layers of aqueous adhesive layers 12 and one layer of first ceramic coating 13; and one layer of the aqueous adhesive layer 12 is in direct contact with the first negative electrode material layer 32. The second separator 20 includes a second base film 21, an oily adhesive layer 22 and a second ceramic coating 23. The oily adhesive layer 22 is arranged on both sides of the second base film 21, and the second ceramic coating 23 is arranged on the side of the second base film 21 away from the second negative electrode material layer 33. The second ceramic coating 23 is located between the second base film 21 and the oily adhesive layer 22. That is, the second separator 20 includes two layers of oily adhesive layers 22 and one layer of second ceramic coating 23, and one layer of oily adhesive layer 22 is in direct contact with the second negative electrode material layer 33. The positive electrode sheet 40 includes a positive electrode collector 41 and positive electrode material layers arranged on both surfaces of the positive electrode collector 41. The positive electrode material layer includes a first positive electrode material layer 42 and a second positive electrode material layer 43.
[0030] In some embodiments of the present application, the first diaphragm 10 includes a water-based adhesive layer 12 and a first ceramic coating layer 13, the water-based adhesive layer 12 is in direct contact with the first negative electrode material layer 32, and the first ceramic coating layer 13 is arranged on the side of the first base membrane 11 away from the first negative electrode material layer 32; the second diaphragm 20 includes an oily adhesive layer 22 and a second ceramic coating layer 23, the oily adhesive layer 22 is in direct contact with the second negative electrode material layer 33, and the second ceramic coating 23 is arranged on the side of the second base membrane 21 away from the second negative electrode material layer 33.
[0031] like Figure 1 and Figure 3As shown, in one winding circle of the electrode assembly 100, the positive electrode sheet 40 is farther from the winding center of the electrode assembly 100 than the negative electrode sheet 30, and the first negative electrode material layer 32 is closer to the positive electrode sheet 40 than the second negative electrode material layer 33, so that the first negative electrode material layer 32 is closer to the outside of the electrode assembly 100 than the second negative electrode material layer 33. In one winding circle of the electrode assembly 100, the first negative electrode material layer 32 located on the outside is wrapped by the positive electrode sheet 40, the winding radius of the positive electrode sheet 40 is greater than the winding radius of the first negative electrode material layer 32, the positive-negative electrode ratio (CellBalance, CB, the ratio of the negative electrode capacity per unit area to the positive electrode capacity per unit area) at the first negative electrode material layer 32 is smaller, the first negative electrode material layer 32 side is more prone to lithium deposition, and the interface problem is more likely to occur than the second negative electrode material layer 33 side on the inside. Based on this, adding the first ceramic coating 13 on the side of the first diaphragm 10 close to the positive electrode plate 40 is beneficial to improve the liquid retention capacity of the first diaphragm 10 close to the positive electrode plate 40, thereby improving the lithium deposition problem and interface problem on the side of the first negative electrode material layer 32, and further improving the cycle performance of the secondary battery. In the entire winding structure of the electrode assembly 100, there is a situation where the second positive electrode material layer 43 is in direct contact with the second diaphragm 20. Since the second positive electrode material layer 43 has the risk of falling powder and causing a short circuit, a second ceramic coating 23 is set on the side of the second diaphragm 20 close to the second positive electrode material layer 43 in the winding structure. The second ceramic coating 23 has a high liquid retention capacity, which can reduce the probability of the second positive electrode material layer 43 falling powder and causing a short circuit risk, which is beneficial to further improve the safety performance of the secondary battery. In addition, the second ceramic coating 23 also has good wetting properties, which can promote the transmission of the electrolyte during the cycle, which is beneficial to further improve the cycle performance of the secondary battery. Therefore, the first separator 10 and the second separator 20 with different characteristics are used in the electrode assembly 100, and each of them exerts different advantages, so that the cycle performance and safety performance of the secondary battery can be taken into account.
[0032] In some embodiments of the present application, Figure 3 and Figure 4As shown, in the corner area 101 of the electrode assembly 100, a corner section of a positive electrode sheet 40 is adjacent to a corner section of a first negative electrode material layer 32, the corner section of the positive electrode sheet 40 is farther from the winding center of the electrode assembly 100 than the corner section of the first negative electrode material layer 32, and the first separator 10 is located between the corner section of the positive electrode sheet 40 and the corner section of the first negative electrode material layer 32. That is, in a corner section of a winding circle of the electrode assembly 100, the positive electrode sheet 40 is farther from the winding center of the electrode assembly 100 than the negative electrode sheet 30, and the first negative electrode material layer 32 is closer to the positive electrode sheet 40 than the second negative electrode material layer 33, so that the first negative electrode material layer 32 is closer to the outside of the electrode assembly 100 than the second negative electrode material layer 33. In the corner section of a winding circle of the electrode assembly 100, the first negative electrode material layer 32 located on the outside is wrapped by the positive electrode sheet 40, the winding radius of the positive electrode sheet 40 is greater than the winding radius of the first negative electrode material layer 32, the positive-negative electrode ratio (CB) at the first negative electrode material layer 32 is small, the first negative electrode material layer 32 side is more prone to lithium deposition, and is more prone to interface problems than the second negative electrode material layer 33 side on the inside, and the corner area 101 is more prone to lithium deposition and interface problems than the straight area 102. Based on this, adding the first ceramic coating 13 to the side of the first diaphragm 10 close to the positive electrode sheet 40 is conducive to improving the liquid retention capacity of the first diaphragm 10 close to the positive electrode sheet 40, thereby helping to improve the lithium deposition problem and interface problem on the side of the first negative electrode material layer 32 in the corner area 101. In the entire winding structure of the electrode assembly 100, there is a situation where the second positive electrode material layer 43 is in direct contact with the second diaphragm 20. Since the corner area 101 is more prone to powder loss than the straight area 102, that is, the second positive electrode material layer 43 in the corner area 101 has a higher risk of powder loss and causing a short circuit. In the corner area 101 of the winding structure, the second diaphragm 20 is arranged on the side close to the second positive electrode material layer 43. The second ceramic coating 23 has a high liquid retention capacity, which can reduce the probability of the second positive electrode material layer 43 in the corner area 101 causing a short circuit risk due to powder loss, which is conducive to further improving the safety performance of the secondary battery. In addition, the second ceramic coating 23 also has good wetting properties, which can promote the transmission of the electrolyte during the cycle process, and can also reduce the risk of electrolyte bridge breakage in the area near the second positive electrode material layer 43 in the corner area 101, which is conducive to further improving the cycle performance of the secondary battery. Therefore, the first diaphragm 10 and the second diaphragm 20 with different characteristics are used in combination in the electrode assembly 100, and each plays a different advantage, which is beneficial to improving the lithium plating problem and interface problem of the secondary battery in the corner area 101, and further improving the cycle performance of the secondary battery, so that the cycle performance and safety performance of the secondary battery can be better taken into account.
[0033] In some embodiments of the present application, Figure 2 and Figure 3As shown, along the winding direction W of the electrode assembly 100, the length of the first negative electrode material layer 32 is greater than the length of the second negative electrode material layer 33. In addition, along the winding direction W, one end of the first negative electrode material layer 32 and the second negative electrode material layer 33 are flush, and at the other end, the extension length of the first negative electrode material layer 32 is longer than that of the second negative electrode material layer 33. It can be understood that when the length of the first negative electrode material layer 32 is greater than the length of the second negative electrode material layer 33, it can also be that the extension length of the first negative electrode material layer 32 at one end along the winding direction W and the other end opposite to the winding direction W is longer than that of the second negative electrode material layer 33. The reason for this arrangement is that when the first separator 10 is located on one side of the first negative electrode material layer 32 of the negative electrode plate 30, it is beneficial for the negative electrode plate 30 of the secondary battery to absorb more electrolyte, thereby reducing the risk of lithium deposition at the interface between the electrolyte and the negative electrode plate 30 due to electrolyte bridge breakage in the late cycle of the secondary battery. The present application has no particular limitation on the length difference between the first negative electrode material layer and the second negative electrode material layer, and it can be selected according to the specific situation as long as the purpose of the present application can be achieved.
[0034] In some embodiments of the present application, the aqueous adhesive layer includes an aqueous adhesive, and the aqueous adhesive includes at least one of aqueous polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber or aqueous polyacrylate, so that the aqueous adhesive layer in the present application can be obtained. Moreover, it is beneficial to improve the bonding force between the first diaphragm and the positive electrode plate, between the first diaphragm and the negative electrode plate, and strengthen the interface between the first diaphragm and the positive electrode plate, and between the first diaphragm and the negative electrode plate, so as to facilitate the transmission of lithium ions and improve the cycle performance of the secondary battery. In addition, it is also beneficial to reduce the possibility of the first ceramic coating falling off and improve the safety performance of the secondary battery. The present application has no special restrictions on the weight average molecular weight of the aqueous adhesive, as long as the purpose of the present application can be achieved. For example, the weight average molecular weight of the aqueous adhesive can be 1.5×10 4 to 9×10 6 .
[0035] In some embodiments of the present application, the coating weight CW1 of the aqueous adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm 2 For example, the coating weight CW1 of the aqueous adhesive layer may be 0.0004 mg / mm 2 , 0.0006mg / mm 2 , 0.0008mg / mm 2 , 0.001mg / mm 2 , 0.0012mg / mm 2 , 0.0014mg / mm 2 , 0.0016mg / mm 2 、0.0018mg / mm2 , 0.002mg / mm 2 Or a range consisting of any two of the above values. By adjusting the coating weight CW1 of the aqueous adhesive layer within the scope of the present application, the first diaphragm and the positive electrode sheet and / or the negative electrode sheet have a higher bonding force, which can strengthen the interface between the first diaphragm and the positive electrode sheet and / or the negative electrode sheet, which is beneficial to the transmission of lithium ions and can further improve the cycle performance of the secondary battery.
[0036] In some embodiments of the present application, the oily adhesive layer includes an oily adhesive, and the oily adhesive includes at least one of oily polyvinylidene fluoride, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer, so that the oily adhesive layer in the present application can be obtained. Moreover, it is beneficial to improve the bonding force between the second diaphragm and the positive electrode plate, between the second diaphragm and the negative electrode plate, and strengthen the interface between the second diaphragm and the positive electrode plate, and between the second diaphragm and the negative electrode plate, so as to facilitate the transmission of lithium ions and improve the cycle performance of the secondary battery. In addition, it is also beneficial to reduce the possibility of the second ceramic coating falling off and improve the safety performance of the secondary battery. The present application does not have any special restrictions on the weight average molecular weight of the oily adhesive, as long as the purpose of the present application can be achieved. For example, the weight average molecular weight of the oily adhesive can be 1.5×10 4 to 9×10 6 In the present application, the oily polyvinylidene fluoride may include but is not limited to at least one of KYNAR PVDF lithium-ion battery binder (Kynar761A), PVDF5130 or HSV900; the model of Kynar 761A may include but is not limited to HSV761, HSV761A, HSV301F, HSV2801, HSVLBG, etc.
[0037] For water-based polyvinylidene fluoride and oil-based polyvinylidene fluoride, the morphology of polyvinylidene fluoride in water-based solvents and oil-based organic solvents is different. In water-based solvents, polyvinylidene fluoride is spherical, and in oil-based organic solvents, the molecular chain of polyvinylidene fluoride is opened into a chain, so its adhesion is better. Water-based polyvinylidene fluoride and oil-based polyvinylidene fluoride can be distinguished by observing the morphology of the adhesive under a scanning electron microscope (SEM).
[0038] In some embodiments of the present application, the coating weight CW2 of the oily adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm 2 For example, the coating weight CW2 of the oily adhesive layer may be 0.0004 mg / mm 2 , 0.0006mg / mm 2 , 0.0008mg / mm 2 、0.001mg / mm 2, 0.0012mg / mm 2 , 0.0014mg / mm 2 , 0.0016mg / mm 2 、0.0018mg / mm 2 , 0.002mg / mm 2 Or a range consisting of any two of the above values. By adjusting the coating weight CW2 of the oily adhesive layer within the scope of the present application, the second diaphragm has a higher bonding force with the positive electrode sheet and / or the negative electrode sheet, which can strengthen the interface between the second diaphragm and the positive electrode sheet and / or the negative electrode sheet, which is beneficial to the transmission of lithium ions and can further improve the cycle performance of the secondary battery.
[0039] In one embodiment of the present application, the aqueous adhesive layer may further include a first thickener, and the oily adhesive layer may further include a second thickener. The first thickener is applied to the aqueous adhesive layer, and the second thickener is applied to the oily adhesive layer, which is conducive to increasing the stability of the aqueous adhesive layer slurry and the oily adhesive layer slurry, and preventing the sedimentation of each component in the aqueous adhesive layer slurry and the oily adhesive layer slurry. The present application has no particular restrictions on the types of the first thickener and the second thickener, as long as the purpose of the present application can be achieved. For example, the first thickener and the second thickener are each independently selected from at least one of hydroxyethyl cellulose, methyl hydroxyethyl cellulose, sodium carboxymethyl cellulose, polyacrylamide or sodium alginate. The present application has no particular restrictions on the content of the first thickener in the aqueous adhesive layer and the content of the second thickener in the oily adhesive layer. Those skilled in the art can make a selection according to actual needs, as long as the purpose of the present application can be achieved. For example, based on the mass of the aqueous adhesive layer, the mass percentage of the first thickener is 0.3% to 6%; based on the mass of the oily adhesive layer, the mass percentage of the second thickener is 0.3% to 6%. This application does not specifically limit the content of the aqueous adhesive in the aqueous adhesive layer and the content of the oily adhesive in the oily adhesive layer. Those skilled in the art can choose according to actual needs as long as the purpose of this application can be achieved. For example, based on the mass of the aqueous adhesive layer, the mass percentage of the aqueous adhesive is 94% to 99.7%; based on the mass of the oily adhesive layer, the mass percentage of the oily adhesive is 94% to 99.7%.
[0040] In some embodiments of the present application, the coating weight CW1' of the first ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 For example, the coating weight CW1' of the first ceramic coating may be 7 mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm2 , 9.2mg / cm 2 、9.5mg / cm 2 、9.7mg / cm 2 、10mg / cm 2 、10.2mg / cm 2 、10.5mg / cm 2 、10.7mg / cm 2 、11mg / cm 2 , 11.2mg / cm 2 、11.5mg / cm 2 、11.7mg / cm 2 , 12mg / cm 2 、12.5mg / cm 2 、13mg / cm 2 Or a range consisting of any two of the values. By regulating the coating weight CW1' of the first ceramic layer within the above range, the first ceramic coating can absorb part of the electrolyte. Regulating the coating weight of the first ceramic layer within the above range is beneficial to increasing the liquid retention of the first diaphragm, thereby improving the liquid storage performance of the first diaphragm, and is beneficial to improving the cycle performance of the secondary battery. At the same time, it is beneficial to improve the thermal stability and strength of the first diaphragm, improve its mechanical properties, reduce the possibility of large-area contact between the positive electrode and the negative electrode due to the shrinkage of the first diaphragm during the charging and discharging of the secondary battery, and is beneficial to improving the safety performance of the secondary battery.
[0041] In some embodiments of the present application, based on the mass of the first ceramic coating, the mass percentage C1 of the first ceramic particles is 10% to 50%. For example, the mass percentage C1 of the first ceramic particles is 10%, 20%, 25%, 30%, 36%, 42%, 50% or any value between any two of the above numerical ranges. The mass percentage of the first ceramic particles in the first ceramic coating is regulated within the above range so that the first ceramic particles can fully play their corresponding role, and a first diaphragm with good liquid storage capacity and wetting performance is obtained. The first diaphragm is applied to the secondary battery, which is beneficial to the secondary battery having good cycle performance, while taking into account the energy density and safety performance of the secondary battery.
[0042] In some embodiments of the present application, the coating weight CW2' of the second ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 For example, the coating weight CW2' of the second ceramic coating may be 7 mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm2 , 9.2mg / cm 2 、9.5mg / cm 2 、9.7mg / cm 2 、10mg / cm 2 、10.2mg / cm 2 、10.5mg / cm 2 、10.7mg / cm 2 、11mg / cm 2 , 11.2mg / cm 2 、11.5mg / cm 2 、11.7mg / cm 2 , 12mg / cm 2 、12.5mg / cm 2 、13mg / cm 2 Or a range consisting of any two of the values. By regulating the coating weight CW2' of the second ceramic layer within the above range, it is beneficial to improve the thermal stability and strength of the second diaphragm, improve its mechanical properties, reduce the possibility of large-area contact between the positive electrode and the negative electrode due to the shrinkage of the second diaphragm during the charging and discharging of the secondary battery, and help improve the safety performance of the secondary battery. At the same time, the second ceramic coating can absorb part of the electrolyte. Regulating the coating weight of the second ceramic layer within the above range is beneficial to increase the liquid retention of the second diaphragm, thereby improving the liquid storage performance of the second diaphragm, which is beneficial to further take into account the cycle performance of the secondary battery.
[0043] In some embodiments of the present application, based on the mass of the second ceramic coating, the mass percentage C2 of the second ceramic particles is 10% to 50%. For example, the mass percentage C2 of the second ceramic particles is 10%, 20%, 25%, 30%, 36%, 42%, 50% or any value between any two of the above numerical ranges. The mass percentage of the second ceramic particles in the second ceramic coating is regulated within the above range, so that the second ceramic particles can fully play their corresponding role, so that the second diaphragm can take into account the liquid retention capacity, and the second diaphragm is applied to the secondary battery, which is conducive to making the secondary battery have high energy density and safety performance, and taking into account the cycle performance of the secondary battery.
[0044] In some embodiments of the present application, the first ceramic coating includes first ceramic particles, the second ceramic coating includes second ceramic particles, and the first ceramic particles and the second ceramic particles each independently include at least one of aluminum oxide, boehmite, silicon oxide, magnesium oxide, titanium oxide, tin oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, or calcium hydroxide. The type of the first ceramic particles in the first ceramic coating and the type of the second ceramic particles in the second ceramic coating are within the scope of the present application, which can further improve the liquid retention capacity of the first diaphragm and the second diaphragm, improve the interface problem caused by insufficient electrolyte between the positive electrode and the negative electrode, and thus further improve the cycle performance of the secondary battery.
[0045] In one embodiment of the present application, the first ceramic coating also includes a first ceramic coating binder, and the second ceramic coating also includes a second ceramic coating binder. The present application does not particularly limit the types of the first ceramic coating binder and the second ceramic coating binder, as long as the purpose of the present application can be achieved. For example, the first ceramic coating binder and the second ceramic coating binder are each independently selected from at least one of styrene-butadiene rubber, polyvinyl alcohol, polyvinylidene fluoride, polyacrylic acid, polymethyl methacrylate, polybutyl acrylate or polyacrylonitrile. The present application does not particularly limit the content of the first ceramic particles and the first ceramic coating binder in the first ceramic coating, and the content of the second ceramic particles and the second ceramic coating binder in the second ceramic coating. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. Exemplarily, based on the mass of the first ceramic coating, the mass percentage of the first ceramic coating binder is 50% to 90%; based on the mass of the second ceramic coating, the mass percentage of the second ceramic coating binder is 50% to 90%.
[0046] In some embodiments of the present application, the porosity P1 of the first base film is greater than the porosity P2 of the second base film, 40% ≤ P1 ≤ 70%, 5% ≤ P2 ≤ 50%. In some embodiments of the present application, 50% ≤ P1 ≤ 60%, 10% ≤ P2 ≤ 40%. For example, P1 can be 40%, 45%, 50%, 55%, 60%, 65%, 70% or a range consisting of any two values therebetween. For example, P2 can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two values therebetween. The first base film has a higher porosity than the second base film, which can further increase the liquid retention of the first diaphragm, which is beneficial to improve the interface problems caused by insufficient electrolyte between the positive and negative electrode sheets, thereby further improving the cycle performance of the secondary battery. At the same time, by adjusting the porosity P1 of the first base film and the porosity P2 of the second base film within the scope of the present application, the mechanical strength of the first separator and the second separator is relatively high, and the safety performance of the secondary battery can be further taken into account.
[0047] In some embodiments of the present application, the aperture D1 of the first base film is larger than the aperture D2 of the second base film, 80nm≤D1≤700nm, 50nm≤D2≤200nm. In some embodiments of the present application, 250nm≤D1≤520nm, 100nm≤D2≤150nm. For example, D1 can be 80nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, or a range consisting of any two values therebetween. For example, D2 can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 120nm, 150nm, 180nm, 200nm, or a range consisting of any two values therebetween. The first base film has a larger pore size than the second base film, which can increase the liquid retention of the first diaphragm and improve the transmission of lithium ions, which is beneficial to improve the interface problem caused by insufficient electrolyte between the positive electrode and the negative electrode in the corner area, thereby further improving the cycle performance of the secondary battery. At the same time, by adjusting the pore size D1 of the first base film and the pore size D2 of the second base film within the scope of this application, the mechanical strength of the first diaphragm and the second diaphragm is relatively high, which can further take into account the safety performance of the secondary battery.
[0048] In some embodiments of the present application, the thickness H1 of the first diaphragm is 7.5 μm to 15.0 μm, and the thickness H2 of the second diaphragm is 6.0 μm to 13.0 μm. For example, the thickness H1 of the first diaphragm can be 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, 10.5 μm, 11.0 μm, 11.5 μm, 12.0 μm, 12.5 μm, 13.0 μm, 13.5 μm, 14.0 μm, 14.5 μm, 15.0 μm, or a range consisting of any two values therebetween. For example, the thickness H2 of the second diaphragm can be 6.0 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11.0 μm, 11.5 μm, 12.0 μm, 12.5 μm, 13.0 μm, or a range consisting of any two values therebetween. By regulating the thickness H1 of the first diaphragm and the thickness H2 of the second diaphragm within the above range, the obtained secondary battery has a high energy density while taking into account both cycle performance and safety performance.
[0049] In some embodiments of the present application, the thickness h1 of the first base film may be 4.5 μm to 8.0 μm, and the thickness h2 of the second base film may be 4.5 μm to 8.0 μm. The present application does not particularly limit the types of the first base film and the second base film, as long as the purpose of the present application can be achieved. For example, the materials of the first base film and the second base film may include but are not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The types of the first base film and the second base film may include at least one of a woven film, a nonwoven film, a microporous film, a composite film, a rolled film or a spun film.
[0050] In the present application, the first base film with different porosity and pore size can be purchased, and the first base film with the required porosity and pore size can be selected in combination with the "porosity test" and "pore size test" test methods of the present application. The second base film with different porosity and pore size can be purchased, and the second base film with the required porosity and pore size can be selected in combination with the "porosity test" and "pore size test" test methods of the present application.
[0051] The present application has no particular restrictions on the preparation method of the first diaphragm, as long as the purpose of the present application can be achieved. For example, the preparation method of the first diaphragm includes but is not limited to the following steps: (1) adding the first binder and the first thickener into deionized water and mixing them evenly to obtain an aqueous bonding layer slurry; (2) adding the first ceramic particles and the first ceramic coating binder into deionized water and mixing them evenly to obtain a first ceramic coating slurry; (3) coating the first ceramic coating slurry on one surface of the first base film, and after drying, forming a first ceramic coating on one surface of the first base film; then coating the aqueous bonding layer slurry on the surface of the first ceramic coating away from the first base film, and after drying, forming an aqueous bonding layer on the surface of the first ceramic coating; (4) coating the aqueous bonding layer slurry on the other surface of the first base film, and after drying, forming an aqueous bonding layer on the other surface of the first base film to obtain the first diaphragm. The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved.
[0052] In the present application, the coating weight of the first ceramic coating can be regulated by means known to those skilled in the art. For example, when the first ceramic coating slurry is coated on the surface of the first base film, the coating amount of the first ceramic coating slurry is increased on the basis of a certain solid content of the first ceramic coating slurry to increase the coating weight of the first ceramic coating. On the contrary, the coating weight of the first ceramic coating can be reduced. The coating weight of the water-based adhesive layer can be regulated by means known to those skilled in the art. For example, when coating the water-based adhesive layer slurry, the coating amount of the water-based adhesive layer slurry is increased on the basis of a certain solid content of the water-based adhesive layer slurry to increase the coating weight of the water-based adhesive layer. On the contrary, the coating weight of the water-based adhesive layer can be reduced.
[0053] The present application has no particular restrictions on the preparation method of the second diaphragm, as long as the purpose of the present application can be achieved. For example, the preparation method of the second diaphragm includes but is not limited to the following steps: (1) adding the second binder and the second thickener to N-methylpyrrolidone (NMP) and mixing them evenly to obtain an oily bonding layer slurry; (2) adding the second ceramic particles and the second ceramic coating binder to N-methylpyrrolidone and mixing them evenly to obtain a second ceramic coating slurry; (3) coating the second ceramic coating slurry on one surface of the second base film, and after drying, forming a second ceramic coating on one surface of the second base film; then coating the oily bonding layer slurry on the surface of the second ceramic coating away from the second base film, and after drying, forming an oily bonding layer on the surface of the second ceramic coating; (4) coating the oily bonding layer slurry on the other surface of the second base film, and after drying, forming an oily bonding layer on the other surface of the second base film to obtain a second diaphragm. The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved.
[0054] In the present application, the coating weight of the oily adhesive layer can be regulated by means known to those skilled in the art. For example, when the oily adhesive layer slurry is coated on the surface of the second base film or the second ceramic coating, the coating amount of the oily adhesive layer slurry is increased on the basis of a certain solid content of the oily adhesive layer slurry to increase the coating weight of the oily adhesive layer. On the contrary, the coating weight of the oily adhesive layer can be reduced. The coating weight of the second ceramic coating can be regulated by means known to those skilled in the art. For example, when coating the second ceramic coating slurry, the coating amount of the second ceramic coating slurry is increased on the basis of a certain solid content of the second ceramic coating slurry to increase the coating weight of the second ceramic coating. On the contrary, the coating weight of the second ceramic coating can be reduced.
[0055] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector, illustratively, the composite current collector can be a lithium copper composite current collector, a carbon copper composite current collector, a nickel copper composite current collector, a titanium copper composite current collector, etc. The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4μm to 15μm.
[0056] In some embodiments of the present application, the first negative electrode material layer and the second negative electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the binder in the first negative electrode material layer and the second negative electrode material layer. Those skilled in the art can choose according to actual needs as long as the purpose of the present application can be achieved. The present application does not particularly limit the thickness of the first negative electrode material layer and the second negative electrode material layer as long as the purpose of the present application can be achieved. For example, the thickness of the first negative electrode material layer and the second negative electrode material layer are each independently 30 μm to 120 μm.
[0057] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0058] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), at least one of lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0059] The positive electrode material layer may also include a conductive agent and a binder. The present application does not particularly limit the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above conductive agent and the above binder. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer. Those skilled in the art can select according to actual needs, as long as the purpose of the present application can be achieved.
[0060] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.
[0061] In the present application, the secondary battery further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0062] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, lithium salts may include but are not limited to LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 , Li 2 SiF 6 At least one of lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular limitation on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0063] The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0064] The secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0065] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the first diaphragm, the negative electrode sheet, and the second diaphragm in order, winding them to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0066] In some embodiments of the present application, the secondary battery of the present application may include but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery, etc. In some embodiments of the present application, the secondary battery includes a lithium ion battery.
[0067] The second aspect of the present application provides an electric device, which includes the secondary battery in any of the above embodiments. Therefore, the electric device provided by the present application has good performance.
[0068] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0069] Example
[0070] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0071] Test methods and equipment:
[0072] First and second diaphragm sampling methods:
[0073] The lithium-ion batteries in the tested embodiments and comparative examples were disassembled, the first diaphragm and the second diaphragm were taken out, and the electrolyte residue was removed by soaking in dimethyl carbonate (DMC) for 20 minutes, and then the first diaphragm and the second diaphragm were placed in an oven and dried at 60°C for 12 hours to obtain the first diaphragm sample and the second diaphragm sample. The above method was used to obtain the first diaphragm and the second diaphragm in the following tests unless otherwise specified.
[0074] Sampling method of the first basement membrane and the second basement membrane:
[0075] The first diaphragm and the second diaphragm obtained by the above sampling were placed in containers respectively, N-methylpyrrolidone (NMP) was added, and the containers were placed in an ultrasonic instrument with a heating function for ultrasonication, the temperature was controlled at 45°C, and the ultrasonication was performed for 3 hours. When the first diaphragm and the second diaphragm became completely transparent, they were taken out to obtain the first basement membrane and the second basement membrane. The above method was used to obtain the first basement membrane and the second basement membrane in the following tests unless otherwise specified.
[0076] Porosity test of the first base film and the second base film:
[0077] The gas displacement method is used for testing. The first base film and the second base film are punched out by a mold to prepare samples (the technicians in this field can select the molds with common sizes and shapes in this field according to the size, shape, test equipment requirements and other factors of the test object). The true volume V of the sample is measured by a true density tester. 0 The apparent volume V of the sample can be calculated by measuring the area and thickness of the sample, then the percentage of the sample pore volume to the total area P = (VV 0 ) / V×100%, that is, the porosity of the first base film or the second base film is obtained respectively.
[0078] Pore size test of the first base film and the second base film:
[0079] The specific steps are as follows:
[0080] ① Use anhydrous ethanol to completely wet and fill the pores of the base membrane to be tested, so that positive pressure is formed in the pores due to capillary phenomenon;
[0081] ②Put the basement membrane into a closed tank and use gas pressure to squeeze the liquid out of the capillary pores;
[0082] ③ According to the relative relationship between the pressure ΔP applied when the liquid in a single pore is completely squeezed out of the capillary pore and the pore diameter d, the diaphragm pore diameter can be obtained according to the Laplace equation. The Laplace equation is shown as follows:
[0083] d=-4γcosθ / ΔP×100%
[0084] Wherein, d is the pore diameter (aperture), ΔP is the pressure, γ is the surface tension of anhydrous ethanol, and θ is the contact angle between the diaphragm and anhydrous ethanol. At different pressures, the liquid in the basement membrane will be squeezed out successively and a certain gas penetration flow rate will be generated. The pore size and pore size distribution can be calculated based on the relationship between pressure and flow changes. The above basement membrane is the first basement membrane or the second basement membrane.
[0085] Thickness test of the first and second diaphragms:
[0086] The first diaphragm was subjected to argon ion polishing to obtain a cross section of the first diaphragm, and the cross section of the first diaphragm along the thickness direction was observed by a field emission scanning electron microscope (Philips, XL-30 model) and a scanning electron microscope photograph was taken, and the thickness H1 of the first diaphragm was measured by the scanning electron microscope. The first diaphragm was replaced by the second diaphragm, and the thickness H2 of the second diaphragm was measured.
[0087] Capacity retention test:
[0088] A battery performance tester (brand: Xinweier; model: CT-4008W-5V6A-80CH) was used to perform constant current charging with a current of 4A (charging rate of 1C) to a full charge voltage of 4.5V, and then to perform constant voltage charging with a current of 4.5V to a cut-off current of 200mA (0.05C), followed by standing for 10 minutes, and then to perform constant current discharge with a current of 2A (0.5C) to a voltage of 3V, and to stand for 10 minutes. This process was recorded as 1 cycle, and at this time there would be a discharge capacity of 1 cycle; then the charge and discharge were repeated. Among them, the discharge capacity of the first discharge is the initial discharge capacity.
[0089] Capacity retention rate (%)=(discharge capacity at the 1000th cycle / discharge capacity at the first cycle)×100%.
[0090] Extrusion test:
[0091] At 25℃, charge the lithium-ion battery to 4.5V at 2C, and then charge it to 0.02C at 4.5V. Place the lithium-ion battery on the test table at 20±5℃, with 5 lithium-ion batteries facing up and 5 lithium-ion batteries facing up (along the thickness of the lithium-ion battery, one side is the front side and the other side is the back side). Use a blunt nail with a diameter of 6mm, a drop speed of 300N / min, and an extrusion force of 2000N. Test the battery 12mm away from the top seal. Judgment criteria: If there is no fire or explosion, the extrusion test is considered to have passed. Each group tests 10 lithium-ion batteries, and the final result is recorded as "number of passed batteries / 10".
[0092] Example 1-1
[0093] <Preparation of First Separator>
[0094] A polyethylene (PE) film with a thickness of h1 = 5 μm is used as the first base film, the porosity P1 of the first base film is 55%, and the pore size D1 of the first base film is 380 nm.
[0095] Water-based polyvinylidene fluoride (water-based PVDF, Mw = 8.3 × 10 6 ) and the first thickener sodium carboxymethyl cellulose (Mw = 8 × 10 5 ) are mixed in a mass ratio of 98.5:1.5, deionized water is added as a solvent, and after stirring evenly, an aqueous bonding layer slurry with a solid content of 75wt% is formed.
[0096] A water-based adhesive layer slurry is coated on one surface of the first base film, and after drying at 60°C, a water-based adhesive layer is formed on one surface of the first base film; a water-based adhesive layer slurry is coated on the other surface of the first base film, and after drying at 60°C, a water-based adhesive layer is formed on the other surface of the first base film, thereby obtaining a first diaphragm. Based on the mass of the first ceramic coating, the mass percentage C1 of the first ceramic is 30%, and the coating weight CW1' of the first ceramic coating is 9 mg / cm 2 The coating weight of the water-based adhesive layer CW1 is 0.0006 mg / mm 2 .
[0097] <Preparation of Second Separator>
[0098] A polyethylene (PE) film with a thickness of h2 = 5 μm is used as the first base film, the porosity P2 of the second base film is 28%, and the pore size D2 of the second base film is 120 nm.
[0099] The oily binder PVDF5130 (Mw = 8.3 × 10 6 ) and the second thickener sodium carboxymethyl cellulose (Mw = 8 × 10 5 ) are mixed in a mass ratio of 98.5:1.5, N-methylpyrrolidone (NMP) is added as a solvent, and after stirring evenly, an oily bonding layer slurry with a solid content of 75wt% is formed.
[0100] The oily adhesive layer slurry is coated on one surface of the second base film, and after drying at 60°C, an oily adhesive layer is formed on one surface of the second base film; the oily adhesive layer slurry is coated on the other surface of the second base film, and after drying at 60°C, an oily adhesive layer is formed on the other surface of the second base film, thereby obtaining a second diaphragm. Based on the mass of the second ceramic coating, the mass percentage C2 of the first ceramic is 30%, and the coating weight CW2 of the oily adhesive layer is 0.0006 mg / mm 2 The coating weight of the second ceramic coating CW2' is 9 mg / cm 2 .
[0101] <Preparation of negative electrode sheet>
[0102] The negative electrode active materials artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 97.4:1.2:1.4, and then deionized water is added as a solvent. After stirring evenly, a first negative electrode slurry with a solid content of 70wt% is obtained. At the same time, the first negative electrode slurry is also used as the second negative electrode slurry. The first negative electrode slurry is coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 90°C to obtain a negative electrode sheet with a first negative electrode material layer coated with a thickness of 45μm. The second negative electrode slurry is coated on the other surface of the negative electrode current collector copper foil. After drying, the second negative electrode material layer coated on the surface has a thickness of 45μm, thereby obtaining a negative electrode sheet with a total thickness of 96μm. The negative electrode sheet after coating is cold pressed and then cut into a specification of 74mm×824mm for standby use. Among them, the compaction density of the first negative electrode material layer is 1.745g / cm 3 , length is 730mm, and the compaction density of the second negative electrode material layer is 1.745g / cm 3 , with a length of 670 mm, one end of the first negative electrode material layer and the second negative electrode material layer are flush, and the first negative electrode material layer is longer than the second negative electrode material layer at the other end, wherein the other end is the starting end of the winding of the electrode assembly.
[0103] <Preparation of positive electrode sheet>
[0104] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black and the positive electrode binder polyvinylidene fluoride are mixed in a mass ratio of 94:3:3, N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and evenly mixed to form a positive electrode slurry with a solid content of 75wt%. At the same time, the first negative electrode slurry is also used as the second negative electrode slurry. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 90°C to obtain a positive electrode sheet with a first positive electrode material layer coated on one side with a thickness of 50μm. The positive electrode slurry is coated on the other surface of the positive electrode current collector aluminum foil. After drying, the thickness of the second positive electrode material layer coated on the surface is 50μm, that is, a positive electrode sheet with a total thickness of 110μm is obtained. The positive electrode sheet after coating is cold pressed and then cut into a specification of 70mm×800mm for standby use. Among them, the compaction density of the first positive electrode material layer and the second positive electrode material layer is 4.2g / cm 3 .
[0105] <Preparation of Electrolyte>
[0106] In a glove box filled with dry argon atmosphere, propylene carbonate (PC), diethyl carbonate (DEC), and ethylene carbonate (EC) were mixed at a mass ratio of 1.2:1.4:1 to obtain a base solvent, and then lithium hexafluorophosphate (LiPF 6 ) lithium salt is dissolved and mixed thoroughly to obtain an electrolyte. Among them, based on the mass of the electrolyte, LiPF 6 The mass percentage is 12%, and the balance is the base solvent.
[0107] <Preparation of lithium-ion batteries>
[0108] The positive electrode sheet, the first separator, the negative electrode sheet, and the second separator prepared above are stacked in order, and then wound to obtain an electrode assembly. The positive electrode tab is spot welded out with an aluminum tab, and the negative electrode tab is spot welded out with a nickel tab. Among them, the first negative electrode material layer is close to the first separator, the second negative electrode material layer is close to the second separator, and the first positive electrode material layer is close to the first separator and adjacent to the aqueous adhesive layer (the specific structure can be referred to Figure 2 The electrode assembly was placed in an aluminum-plastic film, dried in a vacuum oven at 80°C for 12 hours to remove moisture, and then injected with the above-prepared electrolyte. After vacuum packaging, standing, formation (charging at 0.02C constant current to 3.5V, and then charging at 0.1C constant current to 3.9V), capacity, and shaping processes, a lithium-ion battery was obtained.
[0109] Example 1-2 to Example 1-8
[0110] Except for adjusting the relevant data according to Table 1, the rest is the same as Example 1-1.
[0111] Examples 1-9
[0112] Except for preparing the first diaphragm, the second diaphragm and the lithium ion battery according to the following steps, the rest is the same as Example 1-1:
[0113] <Preparation of First Separator>
[0114] A polyimide microporous membrane with a thickness of h1 = 5 μm is used as the first base membrane. The porosity P1 of the first base membrane is 55%, and the pore size D1 of the first base membrane is 380 nm.
[0115] Water-based polyvinylidene fluoride (water-based PVDF, Mw = 8.3 × 10 6 ) and the first thickener sodium carboxymethyl cellulose (Mw = 8 × 10 5 ) are mixed in a mass ratio of 98.5:1.5, deionized water is added as a solvent, and after stirring evenly, an aqueous bonding layer slurry with a solid content of 75wt% is formed.
[0116] The first ceramic particle aluminum oxide (Al 2 O3 ), the first ceramic coating binder styrene-butadiene rubber (Mw = 7 × 10 6 ) are mixed in a mass ratio of 3:7, deionized water is added as a solvent, and the mixture is stirred evenly to obtain a first ceramic coating slurry with a solid content of 45 wt %.
[0117] A first ceramic coating slurry is coated on one surface of the first base film, and after drying at 60°C, a first ceramic coating is formed on one surface of the first base film; a water-based adhesive layer slurry is coated on the surface of the first ceramic coating away from the first base film, and after drying at 60°C, a water-based adhesive layer is formed on the surface of the first ceramic coating; a water-based adhesive layer slurry is coated on the other surface of the first base film, and after drying at 60°C, a water-based adhesive layer is formed on the other surface of the first base film, thereby obtaining a first diaphragm. Wherein, based on the mass of the first ceramic coating, the mass percentage C1 of the first ceramic is 30%, and the coating weight CW1' of the first ceramic coating is 9 mg / cm 2 The coating weight of the water-based adhesive layer CW1 is 0.0006 mg / mm 2 .
[0118] <Preparation of Second Separator>
[0119] A polyethylene microporous membrane with a thickness of h2 = 5 μm is used as the second base membrane. The porosity P2 of the second base membrane is 28%, and the pore size D2 of the second base membrane is 120 nm.
[0120] The oily binder PVDF5130 (Mw = 8.3 × 10 6 ) and the second thickener sodium carboxymethyl cellulose (Mw = 8 × 10 5 ) are mixed in a mass ratio of 98.5:1.5, N-methylpyrrolidone (NMP) is added as a solvent, and after stirring evenly, an oily bonding layer slurry with a solid content of 75wt% is formed.
[0121] The second ceramic particles are aluminum oxide (Al 2 O 3 ), second ceramic coating binder styrene butadiene rubber (Mw = 7 × 10 6 ) were mixed in a mass ratio of 3:7, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a second ceramic coating slurry with a solid content of 45 wt%.
[0122] An oily adhesive layer slurry is coated on one surface of the second base film, and after drying at 60°C, an oily adhesive layer is formed on one surface of the second base film; a second ceramic coating slurry is coated on the other surface of the second base film, and after drying at 60°C, a second ceramic coating is formed on the other surface of the second base film. An oily adhesive layer slurry is coated on the surface of the second ceramic coating, and after drying at 60°C, an oily adhesive layer is formed on the surface of the second ceramic coating away from the second base film, thereby obtaining a second diaphragm. Wherein, based on the mass of the second ceramic coating, the mass percentage C2 of the first ceramic is 30%, and the coating weight CW2 of the oily adhesive layer is 0.0006 mg / mm 2 The coating weight of the second ceramic coating CW2' is 7 mg / cm 2 .
[0123] <Preparation of lithium-ion batteries>
[0124] The positive electrode sheet, the first separator, the negative electrode sheet, and the second separator prepared above are stacked in order, and then wound to obtain an electrode assembly. The positive electrode tab is spot welded out with an aluminum tab, and the negative electrode tab is spot welded out with a nickel tab. Among them, the first negative electrode material layer is close to the first separator, and the first ceramic coating is located on the side of the first base film away from the first negative electrode material layer; the second negative electrode material layer is close to the second separator, and the second ceramic coating is located on the side of the second base film away from the second negative electrode material layer, and the first positive electrode material layer is close to the first separator and adjacent to the aqueous adhesive layer (the specific structure can be referred to Figure 3 The electrode assembly was placed in an aluminum-plastic film, dried in a vacuum oven at 80°C for 12 hours to remove moisture, and then injected with the above-prepared electrolyte. After vacuum packaging, standing, formation (charging at 0.02C constant current to 3.5V, and then charging at 0.1C constant current to 3.9V), capacity, and shaping processes, a lithium-ion battery was obtained.
[0125] Example 1-10 to Example 1-23
[0126] Except for adjusting the relevant data according to Table 1, the rest is the same as Example 1-9.
[0127] Example 2-1 to Example 2-14
[0128] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.
[0129] Example 2-15 to Example 2-17
[0130] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-10.
[0131] Example 3-1 to Example 3-15
[0132] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-1.
[0133] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-10.
[0134] Comparative Example 1
[0135] Except that the first diaphragm is used to replace the second diaphragm, the rest is the same as Example 1-1.
[0136] Comparative Example 2
[0137] Except for using the second diaphragm to replace the first diaphragm, the rest is the same as Example 1-1.
[0138] Comparative Example 3
[0139] Except that the first diaphragm and the second diaphragm are exchanged, the rest is the same as Example 1-1. The preparation parameters and performance parameters of each example and comparative example are shown in Tables 1 to 3.
[0140] Table 1
[0141]
[0142]
[0143] Note: “ / ” in Table 1 means there is no corresponding parameter.
[0144] It can be seen from Examples 1-1 to 1-23 and Comparative Examples 1 to 3 that the negative electrode sheet is located between the first diaphragm and the second diaphragm, and the first diaphragm is adjacent to the positive electrode sheet, the first diaphragm includes a water-based adhesive layer, and the second diaphragm includes an oily adhesive layer. By using the first diaphragm and the second diaphragm together, the lithium-ion battery can have a high extrusion test pass rate and capacity retention rate at the same time, indicating that the cycle performance and safety performance of the lithium-ion battery can be taken into account. In Comparative Example 1, both diaphragms are the first diaphragm, and the first diaphragm includes a water-based adhesive layer. Although the lithium-ion battery has good cycle performance, its safety performance is poor. In Comparative Example 2, both diaphragms are the second diaphragm, and the second diaphragm includes an oily adhesive layer. Although the lithium-ion battery has good safety performance, its cycle performance is poor. In Comparative Example 3, the first diaphragm and the second diaphragm are swapped. Although the lithium-ion battery has good safety performance, its cycle performance is poor. That is, Comparative Examples 1 to 3 cannot take into account both the cycle performance and safety performance of the lithium-ion battery, while the lithium-ion batteries in Examples 1-1 to 1-23 have good cycle performance and safety performance, indicating that the cycle performance and safety performance of the lithium-ion battery are taken into account.
[0145] The coating weight of the aqueous adhesive layer in the first diaphragm and the coating weight of the oily adhesive layer in the second diaphragm usually affect the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-8 that by regulating the coating weight of the aqueous adhesive layer in the first diaphragm and the coating weight of the oily adhesive layer in the second diaphragm within the scope of the present application, the lithium-ion battery has a high extrusion test pass rate and capacity retention rate, indicating that the cycle performance and safety performance of the lithium-ion battery are taken into account.
[0146] The introduction of the first ceramic coating in the first diaphragm and the second ceramic coating in the second diaphragm usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1-1 to 1-8, 1-10, and 1-14 to 1-20 that the introduction of the first ceramic coating and the second ceramic coating can further improve the capacity retention rate and safety performance of the lithium-ion battery, thereby indicating that the cycle performance and safety performance of the lithium-ion battery are better balanced.
[0147] The coating amount of the first ceramic coating in the first diaphragm and the second ceramic coating in the second diaphragm usually affects the cycle performance of the lithium-ion battery. It can be seen from Examples 1-9 to 1-13 that the coating amount of the first ceramic coating and the second ceramic coating is within the scope of the present application, and the lithium-ion battery has a high extrusion test pass rate and capacity retention rate, indicating that the cycle performance and safety performance of the lithium-ion battery are taken into account.
[0148] The types of aqueous binders and oily binders usually affect the cycle performance of lithium-ion batteries. It can be seen from Examples 1-10, 1-21 to 1-23 that when the types of aqueous binders and oily binders are within the scope of the present application, the lithium-ion batteries have a high extrusion test pass rate and capacity retention rate, indicating that the cycle performance and safety performance of the lithium-ion batteries are taken into account.
[0149] Table 2
[0150]
[0151]
[0152] The porosity of the first base film and the porosity of the second base film usually affect the cycle performance and safety performance of the lithium-ion battery, and have little effect on its energy density. It can be seen from Examples 1-1, 2-1 to 2-14 that by regulating the porosity of the first base film and the porosity of the second base film within the scope of this application, and satisfying that the porosity of the first base film is greater than the porosity of the second base film, the lithium-ion battery has a higher extrusion test pass rate and capacity retention rate, indicating that the cycle performance and safety performance of the lithium-ion battery are taken into account.
[0153] It can be seen from Examples 1-10 and 2-15 to 2-17 that by regulating the porosity of the first base membrane and the porosity of the second base membrane within the scope of the present application and satisfying that the porosity of the first base membrane is greater than the porosity of the second base membrane, the cycle performance and safety performance of the lithium-ion battery can be taken into account.
[0154] Table 3
[0155]
[0156]
[0157] The pore size of the first base film and the pore size of the second base film usually affect the cycle performance and safety performance of the lithium-ion battery, and have little effect on its energy density. It can be seen from Examples 1-1, 3-1 to 3-15 that by adjusting the pore size of the first base film and the pore size of the second base film within the scope of this application, and satisfying that the pore size of the first base film is larger than the pore size of the second base film, the lithium-ion battery has a higher extrusion test pass rate and capacity retention rate, indicating that the cycle performance and safety performance of the lithium-ion battery are taken into account.
[0158] It can be seen from Examples 1-10, 3-16 and 3-18 that by regulating the pore size of the first base membrane and the pore size of the second base membrane within the scope of the present application and satisfying that the pore size of the first base membrane is larger than the pore size of the second base membrane, the cycle performance and safety performance of the lithium-ion battery can be taken into account.
[0159] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery comprising an electrode assembly of a wound structure, wherein the electrode assembly comprises a positive electrode sheet, a negative electrode sheet, a first separator and a second separator, wherein the negative electrode sheet is located between the first separator and the second separator; The negative electrode sheet comprises a negative electrode current collector and a first negative electrode material layer and a second negative electrode material layer located on both sides of the negative electrode current collector in a thickness direction, the first separator is adjacent to the first negative electrode material layer, and the second separator is adjacent to the second negative electrode material layer; The first separator comprises a first base film and a water-based adhesive layer, wherein the water-based adhesive layer is disposed on at least one side of the first base film, wherein one layer of the water-based adhesive layer is in direct contact with the first negative electrode material layer; The second separator includes a second base film and an oily adhesive layer, wherein the oily adhesive layer is disposed on at least one side of the second base film, wherein a layer of the oily adhesive layer is in direct contact with the second negative electrode material layer.
2. The secondary battery according to claim 1, wherein The aqueous adhesive layer is arranged on both sides of the first base film, the first separator further comprises a first ceramic coating, the first ceramic coating is arranged on a side of the first base film away from the first negative electrode material layer, and the first ceramic coating is located between the first base film and the aqueous adhesive layer; and / or, The oily adhesive layer is arranged on both sides of the second base film. The second separator also includes a second ceramic coating, which is arranged on the side of the second base film away from the second negative electrode material layer. The second ceramic coating is located between the second base film and the oily adhesive layer.
3. The secondary battery according to claim 1, wherein Along the winding direction of the electrode assembly, the length of the first negative electrode material layer is greater than the length of the second negative electrode material layer.
4. The secondary battery according to claim 1, wherein The electrode assembly includes a straight area and a corner area. In the corner area, a positive electrode sheet corner segment is adjacent to a first negative electrode material layer corner segment. The positive electrode sheet corner segment is farther away from the winding center of the electrode assembly than the first negative electrode material layer corner segment. The first separator is located between the positive electrode sheet corner segment and the first negative electrode material layer corner segment.
5. The secondary battery according to claim 1, wherein The aqueous adhesive layer includes at least one of aqueous polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber or aqueous polyacrylate; and / or the oily adhesive layer includes at least one of oily polyvinylidene fluoride, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer.
6. The secondary battery according to claim 1, wherein The coating weight CW1 of the aqueous adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm 2 , and / or, the coating weight CW2 of the oily adhesive layer is 0.0004 mg / mm 2 To 0.002mg / mm 2 .
7. The secondary battery according to any one of claims 1 to 6, wherein The porosity P1 of the first base film is greater than the porosity P2 of the second base film, 40%≤P1≤70%, 5%≤P2≤50%.
8. The secondary battery according to claim 7, wherein 50%≤P1≤60%, 10%≤P2≤40%.
9. The secondary battery according to any one of claims 1 to 6, wherein The pore size D1 of the first base film is larger than the pore size D2 of the second base film, 80nm≤D1≤700nm, 50nm≤D2≤200nm.
10. The secondary battery according to claim 9, wherein 250nm≤D1≤520nm, 100nm≤D2≤150nm.
11. The secondary battery according to claim 2, wherein The coating weight CW1' of the first ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 , and / or, the coating weight CW2' of the second ceramic coating is 7 mg / cm 2 Up to 13mg / cm 2 .
12. The secondary battery according to claim 2, wherein The first ceramic coating includes first ceramic particles, and the second ceramic coating includes second ceramic particles, and the first ceramic particles and the second ceramic particles each independently include at least one of aluminum oxide, boehmite, silicon oxide, magnesium oxide, titanium oxide, tin oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide or calcium hydroxide.
13. The secondary battery according to any one of claims 1 to 6, wherein The thickness H1 of the first diaphragm is 7.5 μm to 15.0 μm, and the thickness H2 of the second diaphragm is 6.0 μm to 13.0 μm. 14 . An electric device comprising the secondary battery according to claim 1 .
Citation Information
Cited By
Secondary battery and electronic device
WO2026200029A1
Secondary battery and electronic device
WO2026200045A1
